Recent Advancements in the Riddarholmen Ship Puzzle: A New Interpretation of the Architecture of an Early 16th-Century Clinker-Built Gun-Carrying Warship - Eriksson, Niklas (The international journal of nautical archaeology, 2023)
The 16th-century Riddarholmen Ship was discovered in the middle of Stockholm in 1930. Despite being exhibited since 1947, the efforts to reconstruct the ship have been limited. A substantial portion of the recovered parts has never been put on display. This paper aims to shed new light on the ship´s architecture using the original material from the excavation together with an inventory of the timbers in the collections of the Medieval Museum. From this, it is argued that the ship originally had a full deck, three masts, and a forecastle and that it resembles an early purpose-built, gun-carrying warship.